Synergy between Pelargonium endlicherianum essential oil and conventional antibiotics againstNeisseria meningitidis and Haemophilus influenzae - DAMAR ÇELİK, DAMLA; SOYOĞUL GÜRER, ÜMRAN (ELSEVIER, 2022)
This study investigated the bactericidal effects of the essential oil of Pelargonium endlicherianum in combina-tion with four antibiotics commonly used in the treatment of bacterial meningitis (penicillin, ampicillin, cip-rofloxacin, and gentamicin) against the meningitis causative pathogens Neisseria meningitidis and Haemophilus influenzae. The phagocytic effects of these combinations were also tested against human leuko-cyte cells. The bactericidal effect of P. endlicherianum essential oil (PEO) and antibiotic combinations was dynamically detected by time-kill assay. The function of PEO and antibiotic in permeating outer membrane barriers, when used singly or in combination, was analyzed by UV spectrophotometer. The interactions between antibiotic and essential oil were calculated according to the fractional inhibitory concentration (FIC) index. While a synergistic effect of the ciprofloxacin + PEO combination was determined on N. meningitidis (FIC< 0.5), an additive effect was observed on H. influenzae (FIC= 1). Combined use of PEO with gentamicin showed a synergistic effect against N. meningitidis and H. influenzae (FIC < 0.5). The antimi-crobial effect of the penicillin + PEO combination was higher than that of penicillin + PEO used alone. The ampicillin + PEO combination had a synergistic effect on N. meningitidis and an additive effect on H. influen-zae. The results of our study showed that the essential oil increases membrane permeability activity and also has phagocytic activity in human leukocyte cells. Combining antibiotics with essential oils that target resis-tant bacteria may open up new options in combating microbial resistance. (c) 2021 SAAB. Published by Elsevier B.V. All rights reserved.
Keywords: Pelargonium endlicherianum; N; meningitides; Antibiotics; Antibacterial activity; Synergism; ANTIMICROBIAL ACTIVITY; CHEMICAL-COMPOSITION; STAPHYLOCOCCUS-AUREUS; ESCHERICHIA-COLI; COMBINATION; STRAINS; ENHANCEMENT; MODE